GOVERNMENT'S NEW POLICY ON THE ARRANGEMENTS OF PARTICIPATING INTEREST - Yulianingsih, Indra; Algasahri, M. Ridwan Yusuf (Faculty of Law Universitas Trunojoyo Madura, 2020)
The Oil and Gas Ministerial Regulation Number 37 of 2016 concerning Provisions for a 10% (ten percent)